THE EFFECT OF WORKPLACE OSTRACISM ON ORGANIZATIONAL SILENCE AND WORKPLACE LONELINESS A STUDY ON HEALTHCARE WORKERS - Ömer Özişli (International Journal of Health Services Research and Policy, 2022)
In the environment of changes in working life and competition, organizations employ their employees by interacting with different individuals. These employees contribute to their organizations by working with many colleagues and managers. This study aims to examine the mediating effect of workplace ostracism on workplace loneliness and organizational silence. Individuals working in health services in public institutions in the Marmara Region constitute the study group. The study data were collected using an online survey method. This study concluded that workplace ostracism has a positive effect on workplace loneliness. Workplace ostracism and workplace loneliness affect organizational silence positively. In addition, workplace loneliness has a mediating role in the effect of workplace ostracism on organizational silence.